Encountering neighbors: coexisting with difference in Auckland's Avondale. Issue 4 (21st April 2022) - Terruhn, Jessica; Ye, Junjia
ABSTRACT: This article discusses neighboring practices across difference in Avondale, a diverse and changing neighbourhood in Auckland, New Zealand. Based on a qualitative study of urban encounters, we draw attention to modes of coexistence in the parochial realm and, more specifically, to encounters with neighbors as an under-researched site of living with difference in cities. In Avondale, adherence to tacit norms of pragmatic, light-touch neighboring is crucial to residents' sense of convivial coexistence and negotiating such rules is regularly inflected with 'difference'. Our findings show that various facets of diversity are salient in enacting neighbourliness. However, class-based differences associated with a recent influx of higher-income earners threw difference into stark relief because newcomers were perceived as deliberately breaching codes of conduct. Our findings demonstrate the importance of accounting for the salience of multiple facets of difference and for conditions of demographic change in developing an understanding of the complexities of neighboring.